Evaluation of Efficiency of Open Rhinoplasty in Correction of Secondary Nasal Deformities Associated with Cleft Lip - خليل عبد الكريم; حسون مراد (Latakia University Journal -Medical Sciences Series, 2020)
Nose deformities associated with cleft lip are considered to be one of the most difficult nose correction procedures. This research aims to correct the secondary nasal deformities associated with cleft lip to secure the aesthetic and functional aspect of the nose and improve the aesthetic proportions of the deformed nose. Sample included 10 patients from the Department of Oral and Maxillofacial Surgery of Tishreen University Hospital-Lattakia during 2017-2018. We took pictures of faces before surgical procedure then Open rhinoplsaty technique was applied to correct nasal deformity according to a protocol and specific steps in the research. After one year post-surgery we took pictures again and we analyzed these images before and after surgery and compared the results with the ideal normative values within the society. We also studied the respiratory function and determine the level of satisfaction of patients aesthetically. The results showed improved in the aesthetic aspect of the nose through the correction of the emergence and rotation of the tip of the nose. This technique did not significantly affect the respiratory function therefore the functional results were satisfactory. This technique has achieved good and satisfying results aesthetically and functionally.